The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2337/dc13-2063
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Glycemic Control and Compliance to Dietary Advice Among Fasting Patients With Diabetes During Ramadan

Abstract: Modified eating habits during the month of Ramadan and the significant increase in food intake after breaking the fast can unbalance the metabolism of patients with diabetes (1-3). Evidence-based guidelines for food intake during Ramadan do not exist. A study was planned to observe the association between different dietary patterns and glycemic control and compliance to dietary advice among fasting patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…It is observed that excessive consumption of sweet and fried food at the end of fasting (Iftar meal) predisposes the patients to hyperglycaemia . Evidence‐based guidelines regarding food intake during Ramadan do not exist . Suggestions given to patients with diabetes regarding diet during Ramadan are usually based on application of general dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that excessive consumption of sweet and fried food at the end of fasting (Iftar meal) predisposes the patients to hyperglycaemia . Evidence‐based guidelines regarding food intake during Ramadan do not exist . Suggestions given to patients with diabetes regarding diet during Ramadan are usually based on application of general dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Using the dietary compliant score 4 In conclusion, with dietary compliance significant reduction in weight can be achieved in people with diabetes and this behavioural change of eating less but according to nutrient needs during Ramadan can be used as motivational factor to reduce weight in the months following Ramadan.…”
Section: Effect Of Ramadan Fasting On the Weight Of Person With Diabetesmentioning
confidence: 99%
“…The Importances of dietary management have been strongly underscored by the diabetes control and complications trial (DCCT) and UK prospective diabetes study (UKPDS) [1][2][3][4][5][6][7][8][9][10]. Although during Ramadan the benefits of fasting appear only in patients who maintain Journal of Nutritional Disorders & Therapy their appropriate diets [9,10], most patients with diabetes find it difficult to understand and comply with the nutritional therapy [9,11].…”
Section: Editorialmentioning
confidence: 99%